2021
DOI: 10.7717/peerj.10644
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate exerts inflammatory bowel disease-like intestinal injury in rats

Abstract: Background Perfluorooctane sulfonate (PFOS), a type of perfluorinated compounds (PFCs), can induce various organ toxicity, including hepatomegaly, immunotoxicity, and gut microbiota disorder. PFCs have been associated with inflammatory bowel disease (IBD). Yet, whether PFOS exposure causes IBD-like disorder and the underlying mechanism remains undefined. Here, we investigated the influence of PFOS exposure on the development of IBD-like disorder in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
14
2
Order By: Relevance
“…For example, 10 mg/kg PFOS exposure was positively associated with the expression levels of IL-1β and TNF-α in rats after 14-day exposure 36 . PFAS can also induce a markable upregulation of proinflammatory cytokines TNF-α expression in the jejunum of the PFOS 1 mg/kg and 10 mg/kg groups compared with the control in rats 37 . Collectively, these results indicated that PFOS exposure induces an upregulated pro-inflammatory infiltration.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, 10 mg/kg PFOS exposure was positively associated with the expression levels of IL-1β and TNF-α in rats after 14-day exposure 36 . PFAS can also induce a markable upregulation of proinflammatory cytokines TNF-α expression in the jejunum of the PFOS 1 mg/kg and 10 mg/kg groups compared with the control in rats 37 . Collectively, these results indicated that PFOS exposure induces an upregulated pro-inflammatory infiltration.…”
Section: Discussionmentioning
confidence: 91%
“…Many in vivo and in vitro experiments have demonstrated that dysregulation of cytokine caused by environmental pollutants induces the inflammatory response 11 , 36 , 37 . For example, 10 mg/kg PFOS exposure was positively associated with the expression levels of IL-1β and TNF-α in rats after 14-day exposure 36 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, 10 mg/kg PFOS exposure was positively associated with the expression levels of IL-1β and TNF-α in rats after 14-day exposure 33 . PFAS can also induce a markable upregulation of proin ammatory cytokines TNF-α expression in the jejunum of the PFOS 1 mg/kg and 10 mg/kg groups compared with the control in rats 34 . Collectively, these results indicated that PFOS exposure induces an upregulated proin ammatory in ltration.…”
Section: Discussionmentioning
confidence: 92%
“…It is noteworthy that when regulating macrophage activation, we also found response to interferon-gamma in the BP of GO enrichment analysis. In fact, macrophage accumulation and inflammatory cytokine infiltration were remarkably increased in rats exposed to PFOS . Furthermore, PFOS exposure may induce distinct tumor necrosis factor-alpha through the upregulation of phosphorylated nuclear factor kappa B p65 expression .…”
Section: Discussionmentioning
confidence: 96%
“…In fact, macrophage accumulation and inflammatory cytokine infiltration were remarkably increased in rats exposed to PFOS. 51 Furthermore, PFOS exposure may induce distinct tumor necrosis factor-alpha through the upregulation of phosphorylated nuclear factor kappa B p65 expression. 52 These findings suggest that M1 polarization of microglia should be studied further.…”
Section: Discussionmentioning
confidence: 99%